Aquaphotomics - Exploring Water Molecular Systems in Nature - Tsenkova, Roumiana; Muncan, Jelena (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint is a compilation of more than 20 scientific publications, both original research papers and review papers, assembled for the Special Issue of Molecules journal, Aquaphotomics; this Special Issue explores water molecular systems in nature, and is the first of its kind organized on this topic. Now available in a reprint, this publication presents cutting-edge research work performed in the area of a young, but rapidly evolving scientific discipline, Aquaphotomics. The reprint includes topics that range from basic water science, material hydration, the water-material interaction and biocompatibility, novel scientific theories about the role of water in cell biology, the possibilities of using Aquaphotomics for monitoring food quality, estimating shelf-life, diagnosing stress in plants, determining diseases in animals and the outcomes of therapies in medicine. The reprint also provides the reader with an opportunity to improve their knowledge in the areas of spectral preprocessing, multivariate analysis and chemometrics, with focus on Aquaphotomics approach. For any reader already working in the field of Aquaphotomics, this will be a highly advantageous publication, in order to ascertain the latest research trends and discoveries; for novices, it offers a window into an exciting new world that is brimming with possibilities.